Identification of Candidate Casein Kinase 2 Substrates in Mitosis by Quantitative Phosphoproteomics - Rusin, Scott F.; Adamo, Mark E.; Kettenbach, Arminja N. (Frontiers in Cell and Developmental Biology, 2017)
Protein phosphorylation is a crucial regulatory mechanism that controls many aspects of cellular signaling. Casein kinase 2 (CK2), a constitutively expressed and active kinase, plays key roles in an array of cellular events including transcription and translation, ribosome biogenesis, cell cycle progression, and apoptosis. CK2 is implicated in cancerous transformation and is a therapeutic target in anti-cancer therapy. The specific and selective CK2 ATP competitive inhibitor, CX-4945 (silmitaseratib), is currently in phase 2 clinical trials. While many substrates and interactors of CK2 have been identified, less is known about CK2 substrates in mitosis. In the present work, we utilize CX-4945 and quantitative phosphoproteomics to inhibit CK2 activity in mitotically arrested HeLa cells and determine candidate CK2 substrates. We identify 330 phosphorylation sites on 202 proteins as significantly decreased in abundance upon inhibition of CK2 activity. Motif analysis of decreased sites reveals a linear kinase motif with aspartic and glutamic amino acids downstream of the phosphorylated residues, which is consistent with known substrate preferences for CK2. To validate specific candidate CK2 substrates, we perform in vitro kinase assays using purified components. Furthermore, we identified CK2 interacting proteins by affinity purification-mass spectrometry (AP-MS). To investigate the biological processes regulated by CK2 in mitosis, we perform network analysis and identify an enrichment of proteins involved in chromosome condensation, chromatin organization, and RNA processing. We demonstrate that overexpression of CK2 in HeLa cells affects proper chromosome condensation. Previously, we found that phosphoprotein phosphatase 6 (PP6), but not phosphoprotein phosphatase 2A (PP2A), opposes CK2 phosphorylation of the condensin I complex, which is essential for chromosome condensation. Here, we extend this observation and demonstrate that PP6 opposition of CK2 is a more general cellular regulatory mechanism.